2001
DOI: 10.1074/jbc.m101495200
|View full text |Cite
|
Sign up to set email alerts
|

Arg1098 Is Critical for the Chloride Dependence of Human Angiotensin I-converting Enzyme C-domain Catalytic Activity

Abstract: Angiotensin (Ang) I-converting enzyme (ACE) is a Zn2؉ metalloprotease with two homologous catalytic domains. Both the N-and C-terminal domains are peptidyl dipeptidases. Hydrolysis by ACE of its decapeptide substrate Ang I is increased by Cl ؊ , but the molecular mechanism of this regulation is unclear. A search for single substitutions to Gln among all conserved basic residues (Lys/Arg) in human ACE C-domain identified R1098Q as the sole mutant that lacked Cl ؊ dependence. Angiotensin I (Ang I) 1 -converting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 21 publications
5
79
1
Order By: Relevance
“…Both ACE activity, and inhibitor affinity for ACE have previously been shown to be dependent on chloride ions, with cACE exhibiting this to a greater extent than nACE 8, 21, 22, 23, 24. As observed with previous structures, all the complexes described here contain the usual two chloride ions bound to cACE, and one to nACE.…”
Section: Resultsmentioning
confidence: 97%
“…Both ACE activity, and inhibitor affinity for ACE have previously been shown to be dependent on chloride ions, with cACE exhibiting this to a greater extent than nACE 8, 21, 22, 23, 24. As observed with previous structures, all the complexes described here contain the usual two chloride ions bound to cACE, and one to nACE.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, site-directed mutagenesis studies suggest that the Cl Ϫ -coordinating ligand Arg 1098 of sACE (Arg 522 of tACE) at the second chloride ion site in tACE (CL2) plays a role in anion activation in sACE (47). The equivalent residue in ACE2 (Arg 514 ) cannot play the same role because this chloride-binding site is replaced in ACE2 with the Glu 398 / Ser 511 double substitution.…”
Section: Resultsmentioning
confidence: 99%
“…The chloride dependence of ACE has long been recognized [25], and most recently mutagenesis studies have shown that it is in fact an arginine residue (Arg1098) that is essential for the chloride activation of ACE [18]. The structure of tACE revealed the location of two buried chloride ions [19].…”
Section: Comparing the Chloride-binding Sites Of Tace And Ace2mentioning
confidence: 99%
“…Most recently, ACE2 has been identified as a functional receptor for the coronavirus which causes the severe acute respiratory syndrome (SARS) [14]. For recent reviews, see [15,16].ACE2 shares a number of characteristics with ACE, both being zinc-containing enzymes which are sensitive to anion activation [4,17,18]. However, unlike ACE, ACE2 functions as a carboxypeptidase and is not susceptible to inhibition by the classical ACE inhibitors [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation